A [two-step/one week] synthesis of C-functionalized homocyclens and cyclams. Application to the preparation of conjugable BCAs without chelating properties alteration1. Issue 104 (11th November 2015) - Camus, Nathalie; Halime, Zakaria; le Bris, Nathalie; Bernard, Hélène; Beyler, Maryline; Platas-Iglesias, Carlos; Tripier, Raphaël
<x xml:space="preserve">Abstract</x> An efficient synthesis of C-functionalized azamacrocycles is presented together with a coordination study showing the week influence of the added appended group.